The association between seeking financial compensation and injury recovery following motor vehicle related orthopaedic trauma. Issue 1 (December 2016) - Murgatroyd, Darnel; Harris, Ian; Tran, Yvonne; Cameron, Ian
Abstract Background Motor vehicle related moderate-severe orthopaedic trauma has a major impact on the burden of injury. In Australia, all states and territories provide access to financial compensation following injury in a motor vehicle crash. The aim of this study was to investigate the influence of seeking financial compensation (i.e., making a claim) on injury recovery following motor vehicle related moderate-severe orthopaedic trauma. Methods Patients admitted with upper/lower extremity fractures after a motor vehicle crash were recruited from two trauma hospitals. Baseline data were collected in person by written questionnaire within two weeks of injury. Follow up data were collected by a mailed written questionnaire at six, 12 and 24 months. Additional (demographic/injury-related) information was collected from hospital databases, all other measures were self-reported. Outcomes were: Short Form-36 Version 2.0 (SF36v2), Physical/Mental Component Scores (PCS/MCS); Post Traumatic Stress Disorder (PTSD) Checklist Civilian Version (PCL-C); and Global Rating of Change (GRC) scale. Analysis involved descriptive statistics and linear mixed models to examine the effect of compensation status on injury recovery over time. Results There were 452 study participants. Baseline characteristics showed: mean age 40 years (17.1 Standard Deviation [SD]); 75 % male; 74 % worked pre-injury; 67 % in excellent-very good pre-injury health; 56 % sustained serious injuries, Injury Severity Score (ISS) 9–15; 61 % had a low-middle range household income. Overall, after controlling for possible confounders, the compensable group had poorer recovery compared to the non-compensable group for PCS (−2.97 Mean Difference (MD), 95 % CI −4.73, −1.22); MCS (−3.44 MD, 95 % CI −5.62, −1.26); PCL-C (3.42MD, 95 % CI 0.87, 5.99); and GRC (−0.66MD, 95 % CI −1.15, −0.17). Injury recovery over time for all participants showed: PCS improved from 6–12 and 12–24 months; MCS and GRC improved from 6–12 months; and PCL-C did not significantly improve from 6–12 and 12–24 months. Injury recovery over time continued for compensable and non-compensable groups but compensable participants had poorer scores at each time period, especially MCS and PCL-C. Conclusions Making a claim was associated with poor injury recovery following motor vehicle related orthopaedic trauma, mainly for mental health. Irrespective of claim status, the majority had poor injury recovery, especially for mental health.